1995
DOI: 10.1016/0014-5793(95)00678-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the affinity of talin and vinculin to charged lipid vesicles: a light scatter study

Abstract: Recent experimental findings have demonstrated that both talin and vinculin bind to phospholipids and insert into the hydrophobic region of lipid membranes. Here, we show that the light scatter method can be used for measuring the affinity of proteins to phospholipid membranes. Large unilamellar DNIPC/ DMPG vesicles were produced by the extrusion technique (LUVETs). We have used repeated heating/cooling scans between 15°C and 35°C to ensure protein-lipid interaction/insertion. A molar affinity of talin, K = 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In calorimetric measurements it was also found that talin, like vinculin, partially inserts into the hydrophobic region of negatively charged lipid bilayers [76]. This finding was later confirmed by light scatter techniques, which yielded a value of 3.3 × 10 5 M −1 for the molar affinity of talin to lipid vesicles [77]. The insertion behaviour of talin into negatively charged lipid bilayers was investigated in more detail by the film balance method combined with fluorescence imaging.…”
Section: Reviewmentioning
confidence: 97%
“…In calorimetric measurements it was also found that talin, like vinculin, partially inserts into the hydrophobic region of negatively charged lipid bilayers [76]. This finding was later confirmed by light scatter techniques, which yielded a value of 3.3 × 10 5 M −1 for the molar affinity of talin to lipid vesicles [77]. The insertion behaviour of talin into negatively charged lipid bilayers was investigated in more detail by the film balance method combined with fluorescence imaging.…”
Section: Reviewmentioning
confidence: 97%